2020
DOI: 10.1016/j.ica.2020.119609
|View full text |Cite
|
Sign up to set email alerts
|

Development of tris-cyclometalated iridium complexes for cellular imaging through structural modification

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…First, the third ligand was replaced by an N^N ligand to change from neutral to a positively charged complex. The prospect of using a cationic cyclometalated iridium(III) compound is desirable since electronic-neutral molecules generally exhibit low water solubility, which usually hampers cell uptake [ 14 , 22 ]. On the other hand, our previous results with bis-cyclometalated iridium(III) compounds demonstrated that slight modifications on benzimidazole-based C^N ligand core rendered high anticancer activities in vitro [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…First, the third ligand was replaced by an N^N ligand to change from neutral to a positively charged complex. The prospect of using a cationic cyclometalated iridium(III) compound is desirable since electronic-neutral molecules generally exhibit low water solubility, which usually hampers cell uptake [ 14 , 22 ]. On the other hand, our previous results with bis-cyclometalated iridium(III) compounds demonstrated that slight modifications on benzimidazole-based C^N ligand core rendered high anticancer activities in vitro [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a water-soluble iridium(III) complex carrying two morpholine units ( 275 ) has been developed for lysosome-targeted imaging and PDT . Kielar and co-workers have demonstrated that iridium(III) complexes containing a pH-sensitive aminoalkyl moiety ( 276 and 277 ) can also specifically target the lysosomes. …”
Section: Luminescent Transition Metal Complexes As Probes For Specifi...mentioning
confidence: 99%